PENGEMBANGAN MATERI AJAR BAHASA ARAB BERBASIS TEMATIK UNTUK ANAK USIA DINI - Nurlaila Nurlaila; Hadiatul Husna (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
This study aims to produce thematic-based Arabic teaching materials for early childhood Arabic learning. The target of the teaching material that has been developed is early childhood students where they learn Arabic at Raudhatul Athfal. Researchers use research and development methods. Data were collected using interview, documentation, and questionnaire. The data obtained from interview and documentation were analyzed qualitatively, while the data obtained from the questionnaire were analyzed quantitatively. The results of the study were thematic-based Arabic teaching materials, namely Arabic teaching materials that have relevance to the themes studied by early childhood students as stated in the Semester Program. The results of product validation indicate that the thematic-based Arabic teaching materials that have been developed are suitable for use in learning Arabic for early childhood students.